2007
DOI: 10.1016/j.jtcvs.2006.09.115
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of cut-and-sew technique for the Cox maze procedure: Comparison with radiofrequency ablation

Abstract: Creating Cox maze lesions with radiofrequency ablation is associated with less freedom from atrial fibrillation both early and late postoperatively. Because transmurality can be assured, the standard cut-and-sew Cox maze procedure remains the gold standard for the surgical treatment of atrial fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 23 publications
1
29
0
Order By: Relevance
“…Surgical studies on the cut-and-sew maze technique 18 have shown that substrate modification at the time of (surgical) PVI almost always eliminates AF, including patients with persistent forms of AF. The difference between the surgical and the radiofrequency current ablation approach is that surgical PVI is permanent, whereas radiofrequency current-induced PVI at the index procedure is associated with a high likelihood of reconduction from the PVs to the LA through gaps in the circumferential ablation lines.…”
Section: The Substrate-modification Strategy Failed To Reduce Arrhythmentioning
confidence: 99%
“…Surgical studies on the cut-and-sew maze technique 18 have shown that substrate modification at the time of (surgical) PVI almost always eliminates AF, including patients with persistent forms of AF. The difference between the surgical and the radiofrequency current ablation approach is that surgical PVI is permanent, whereas radiofrequency current-induced PVI at the index procedure is associated with a high likelihood of reconduction from the PVs to the LA through gaps in the circumferential ablation lines.…”
Section: The Substrate-modification Strategy Failed To Reduce Arrhythmentioning
confidence: 99%
“…Raanani et al ( 2001) recorded sinus rhythm in only 75% of patients a mean of 26 months after Cox maze and mitral valve surgery, which is similar to the Mayo Clinic experience of 74% freedom from AF at 2 years ( Handa et al ,1999;Shaff et al 2000). The use of RF energy for the creation of the atrial lesions of the Cox maze procedure was associated with significantly less freedom from AF both at hospital discharge and at followup (Stulak et al 2007). The differences of the long-term success rate c o u l d b e i n f l u e n c e d o t h e r t h a n b y t h e differences among intraoperative v a r i a b l e s , m a i n l y b y p r e o p e r a t i v e v a r i a b l e s , s u c h a s concomitant valvular surgery and rheumatic valvular heart disease.…”
Section: Literature Reviewmentioning
confidence: 98%
“…However, ablation devices, such as traditional cryoablation, RF ablation, microwave, or ultrasonography, do not necessarily guarantee transmural, continuous necrosis. Although Lall et al 25 noted that AF surgery using an RF ablation device cured AF in >90% of the patients, which is the same as the traditional cut-and-sew maze procedure, Stulak et al 26 and Doty et al 27 reported that the traditional cut-and-sew maze procedure was superior to RF surgery for the treatment of AF. Ishii et al 28 pointed out the importance of complete ablation of the coronary sinus and pulmonary veins during AF surgery.…”
Section: Postoperative Atrial Tachycardiamentioning
confidence: 99%